Austria and Hungary: Different stages of readiness to create added value by using business information systems - Sasvari Peter; Wolf Rauch (PRO PUBLICO BONO - Public Administration, 2014)
It is very important to recognize that the future of e-government cannot be thought through in isolation, it cannot be assessed as a series of administrative tasks or a wider set of measures aimed at making the state more efficient. The administration of today and tomorrow essentially depends on the changes of the economy, society and culture as well. Local governments and public administration serve the interests of citizens and businesses alike, therefore public administration significantly depends on the knowledge, consciousness and mentality of individuals and enterprises, too. However, it is still an open question whether enterprises in Austria and Hungary actually have the IT infrastructure enabling them to adopt the devices of e-governance at a faster pace. The primary objective of this paper is to explore the differences and similarities in the usage of information systems in different size categories in Austria and Hungary. More precisely, it examines how frequently information systems are used in four of the pre-defined size categories (microenterprises, small and medium-sized enterprises and corporations) in both countries. Microenterprises in Hungary hardly used any information systems. When comparing the two countries, the smallest difference could be observed in the use of information systems by corporations.
Keywords: M13; M15; 330; Austria; Hungary; Information systems